Shrimp bacterial and parasitic disease listed in the OIE: A review. (May 2022) - Yu, Young-Bin; Choi, Jae-Ho; Kang, Ju-Chan; Kim, Hyoung Jun; Kim, Jun-Hwan
Abstract: Shrimp aquaculture industry has steadily increased with demand and development of aquaculture technology. In recent years, frequent diseases have become a major risk factor for shrimp aquaculture, such as a drastically reduced the production of shrimp and causing national economic loss. Among them, shrimp bacterial diseases such as hepatopancreatic necrosis disease (AHPND) and necrotizing hepatopancreatitis (NHP–B) and parasitic disease such as Aphanomyces astaci (crayfish plague) are emerging and evolving into new types. OIE (World Organization for Animal Health) regularly updates information on diseases in the Aquatic Code and Aquatic Manual, but in-depth information on the shrimp diseases are lacking. Therefore, the purpose of this review is to provide information necessary for the response and prevention of shrimp diseases by understanding the characteristics and diagnosis of shrimp diseases designated by OIE. Graphical abstract: Image 1 Highlights: Bacterial and parasitic diseases are a major threat to the shrimp aquaculture industry. The pathogens of AHPND and NHP–B, a recetly emerging disease have caused damage to shrimp production. Aphanomyces astaci (Oomycetes) is a fungal-like parasite and one of the world's worst alien species. Identifying bacterial and parasitic shrimp diseases is necessary to properly respond to the diseases.